Effects of processing methods on chemical composition and in vivo digestibility of coffee pulp in Ethiopia - Gebru, G.; Chichaibelu, B.; Reed, J.D. (International Livestock Centre for Africa, 1989)
Effects of the method of processing of coffee cherries on pulp composition and digestibility in vivo were studied. The effects of wet and dry processing on chemical composition were analysed in Experiment 1. The effects of dry processed pulp (Dcop) and wet processed pulp (Wcop) (0 g/d, 60 g/d, 120 g/d and 150 g/d) on intake, digestibility and nitrogen retention in sheep fed hay were determined in Experiment 2. Processing method affected the contents of neutral-detergent fibre (NDF), acid-detergent fibre (ADF), lignin soluble phenolics and insoluble proanthocyanidins (condensed tannins). Dry processed pulp had higher NDF, ADF, lignin and phenolic compounds. There was no effect of pulp level on feed intake or digestibility but N-balance was significantly depressed at the 120 g and 150 g levels of Dcop, at which both urinary and faecal N losses and total urine excretion increased. No pronounced effects were observed for Wcop. Condensed tannins and caffeine in coffee pulp appear to limit its nutritive value.